Clover SA's brand heritage and consumers' price sensitivity and purchase intentions - Goerge, Barbara Refilwe (University of the Witwatersrand, Johannesburg, 2024)
The South African market environment is highly competitive and is characterised by inequality, growing unemployment and rising inflation. The degree of disparity in South Africa’s consumer environment may be the most noticeable aspect as it has one of the highest per-capita expenditure Gini coefficients in the world making it one of the most unequal countries on the planet. Despite this, the country’s gross domestic product (GDP) rate continues to climb by 3.1% in 2021 indicating that despite the prevailing economic and socio-economic issues, the country is seeing a higher flow of revenue and expenditure on goods and services. Consumers are also becoming bombarded with brand communication which increases the level of competition amongst options available to consumers. This makes understanding consumer and shopper behaviour important, more so in terms of the factors that drive purchase intent which is paramount for the success of a brand. In light of this, the research sought to delve into brand heritage and what purpose it serves in in today’s ever-changing economy. Underpinning the research, South Africa premium dairy and milk heritage brand, Clover, was used. With its heritage rooted in South Africa for over 100 years, the intention is to establish whether indeed brand heritage plays a role in purchase intentions for this premium product. Drawing on a comprehensive literature review, the study endeavoured to investigate how brand heritage serves as a significant signalling mechanism for consumers by conveying important information about the quality, consistency and pricing of the brand. This is significant as it helps managers understand the important variables impacting customer purchasing behaviours in South African segment and how to successfully use heritage brands in this market. By employing convenience sampling through a quantitative research methodology, 450 online surveys response were collected and Structural Equation Modelling (SEM) was used to validate the measurements used. Of the six hypotheses, five were supported by the data, however also indicating that price sensitivity does not moderate the relationship between brand heritage and purchase intention. The findings and conclusions provide implications for marketing professionals in the product retail space and further provide suggested areas for future research. It provides actionable recommendations marketers can use when looking to optimise their brand strategies in a competitive marketplace.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Brand heritage; Associated brand quality; Purchase intention; Brand consistency; Authenticity; Price sensitivity; Credibility; Signals; UCTD; SDG-8: Decent work and economic growth